2016
DOI: 10.1111/aji.12511
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic Lymphocyte Immunotherapy for Unexplained Recurrent Spontaneous Abortion: A Meta‐Analysis

Abstract: Allogenic lymphocyte immunotherapy (LIT) as a treatment for unexplained recurrent spontaneous abortion (URSA) is still controversial due to the lack of enough controls to evaluate its effectiveness. Eighteen randomized, placebo-controlled trials with LIT for URSA were included in the meta-analysis. Live birth rates for each group were extracted, and the overall odds ratio (OR) for LIT was calculated. The success rate of treatment group was significantly higher (OR 3.74, 95% CI 3.07 ~ 4.57). LIT performed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 24 publications
1
71
0
5
Order By: Relevance
“…42,43 As pregnancy tissues are the product of both mother and father genes, LIT supports the mother's immune system in the improvement of immunologic tolerance to the genetically foreign pregnancy tissues. 42,43 As pregnancy tissues are the product of both mother and father genes, LIT supports the mother's immune system in the improvement of immunologic tolerance to the genetically foreign pregnancy tissues.…”
Section: Lymphoc Y Te Immunother Apy (Lit )mentioning
confidence: 99%
“…42,43 As pregnancy tissues are the product of both mother and father genes, LIT supports the mother's immune system in the improvement of immunologic tolerance to the genetically foreign pregnancy tissues. 42,43 As pregnancy tissues are the product of both mother and father genes, LIT supports the mother's immune system in the improvement of immunologic tolerance to the genetically foreign pregnancy tissues.…”
Section: Lymphoc Y Te Immunother Apy (Lit )mentioning
confidence: 99%
“…Our team and studies at home and abroad in the past two decades have found that the onset of URSA is mainly related to the disorder of pregnancy immune tolerance. Abnormalities in the quality and quantity of immunocompetent cells at the maternal‐fetal interface are thought to play a crucial role in the progression of URSA . Studies at home and abroad have shown that immunocompetent cells in local tissue of URSA patients are recruited from the periphery blood but not from the self‐renewal of precursor cells, while chemokines and their receptors play initiating and pivotal roles in the recruitment and differentiation of immunocompetent cells.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of the immunotherapy has been controversial [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], but a meta-analysis concerning the immunotherapy for patients with URA reported by the Recurrent Miscarriage Immunotherapy Trialists Group in 1994 [13], Clark in 2008 [7] and 2012 [14] concluded and Liu et al in 2016 [25] concluded that the immunotherapy may be highly effective. In addition, Pandey et al reported a significant improvement in pregnancy outcome in the patient group in their double-blind randomized trial of husband's lymphocyte immunization for women with recurrent spontaneous abortion [19].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy for these patients using their husbands' or a third party's leukocytes has been reported [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Although the efficacy of this modality has been controversial, an analysis of controlled clinical trials revealed the efficacy for patients with Unexplained Recurrent Abortion (URA) [7,14,19,26,27], especially for those who were negative for blocking antibodies evaluated by a mixed lymphocyte culture reaction between spouses (MLR-BAbs) [19,22,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%